STUDI KORELASI KARAKTER PEDULI SOSIAL SISWA DENGAN HASIL BELAJAR PKn SISWA KELAS XI DI SMA NEGERI 12 PEKANBARU - Rada Sulita; Hambali; Ahmad Eddison (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article is derived from the potential that refers to the students’ personality attitudes, one of them is the practice of social care character with students’ Civics Education learning outcomes of class XI at SMA Negeri 12 Pekanbaru. The purpose of the study described in this article was to find out whether there was a correlation between social care characters and the students’ learning outcomes in Civics Education learning subject in class XI at SMA Negeri 12 Pekanbaru. The study was quantitative research with a statistical analysis method namely the Product Moment correlation formula assisted by the IBM SPSS version 20 program. The population of the study was 452 students of class XI at SMA Negeri 12 Pekanbaru. Determination of the sample used the Proportional Random Sampling technique with a number of 68 students of class XI at SMA Negeri 12 Pekanbaru with consideration of Civics Education learning outcomes obtained in class X in semester 2. Data collection methods were observation, interviews, questionnaires and documentation. Based on the statistical hypothesis test, hypothesis Ho was rejected and Ha was accepted. Thus, it could be concluded that there was a correlation of social care character with Civics Education learning outcomes of class XI students at SMAN 12 Pekanbaru with an r-count correlation coefficient 0.650 higher than r-table 0.235. The correlation could be seen from the number of correlation coefficients, the results were positive with an r-count correlation coefficient of 0.650, which was in the range of 0.60-0.799 with the interpretation of "big or strong relationship".